RELATION BETWEEN SERVICE QUALITY AND CUSTOMER SATISFACTION - Agatha Septianna Sri Ratnasari; Antonny Wijaya; Prisca Yeniyati (SIMAK, 2022)
The purpose of this research is to analyze the relation between service qualityand customer satisfaction within Musi Charitas Catholic University. The result of thisstudy will help management to improve service quality and satisfaction among thestudents and hopefully all variables will also fit and match with university values i.e.CHAMPION. 300 questionnaires were distributed to the students from 4 facultiesusing convenience sampling technique, but only 214 questionnaires available to beprocessed. The result shows that Service Quality 61,6% significantly have positiveimpact related to customer satisfaction, and the rest of it 38,4% related with otherfactors.